2020
DOI: 10.1002/eat.23411
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward physical activity as a treatment component for adolescents with anorexia nervosa: An exploratory qualitative study of patient perceptions

Abstract: Objective Anorexia nervosa (AN) with compulsive exercise is associated with poor treatment outcomes. This study sought to understand the attitudes of adolescents with AN from various stages of treatment, toward physical activity research practices and physical activity as a component of treatment. Method Seventeen adolescents 12–18 years old (15 female) with AN (10 with acknowledged history of compulsive exercise) were recruited from a Canadian Tertiary Care Hospital's Eating Disorder Program. Six inpatients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Most identified studies evaluating the relationship between competitiveness and ED treatment and recovery outcomes were qualitative in nature ( n = 12; Chubbs‐Payne et al., 2021; Colton & Pistrang, 2004; De Bois, 2020; Lavis, 2011; Lazerson, 1984; Moreno, 1998; Raulli, 2018; Rich, 2006; Stirling & Kerr, 2012; Warchol, 2013; Warin, 2006; Wasil et al., 2019). Among these, several authors interviewed ED inpatients who reported pressure to compete with others in the ED milieu (Chubbs‐Payne et al., 2021; Colton & Pistrang, 2004; Lavis, 2011; Warchol, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most identified studies evaluating the relationship between competitiveness and ED treatment and recovery outcomes were qualitative in nature ( n = 12; Chubbs‐Payne et al., 2021; Colton & Pistrang, 2004; De Bois, 2020; Lavis, 2011; Lazerson, 1984; Moreno, 1998; Raulli, 2018; Rich, 2006; Stirling & Kerr, 2012; Warchol, 2013; Warin, 2006; Wasil et al., 2019). Among these, several authors interviewed ED inpatients who reported pressure to compete with others in the ED milieu (Chubbs‐Payne et al., 2021; Colton & Pistrang, 2004; Lavis, 2011; Warchol, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Most identified studies evaluating the relationship between competitiveness and ED treatment and recovery outcomes were qualitative in nature ( n = 12; Chubbs‐Payne et al., 2021; Colton & Pistrang, 2004; De Bois, 2020; Lavis, 2011; Lazerson, 1984; Moreno, 1998; Raulli, 2018; Rich, 2006; Stirling & Kerr, 2012; Warchol, 2013; Warin, 2006; Wasil et al., 2019). Among these, several authors interviewed ED inpatients who reported pressure to compete with others in the ED milieu (Chubbs‐Payne et al., 2021; Colton & Pistrang, 2004; Lavis, 2011; Warchol, 2013). For example, participants endorsed perceived competition to be the ‘best anorexic’ while inpatient and described how this disrupts ED recovery and harms relationships with other inpatients (Colton & Pistrang, 2004, p. 311) Additionally, participants reported increased motivation to engage in ED behaviours, such as maladaptive exercise and food restriction, resulting from competitiveness (Colton & Pistrang, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Participants who indicated that they sought ED treatment and left contact information were contacted for the semi-structured interview (n = 36); however, five were excluded after clarifying that they had not sought ED treatment when contacted. The size of the final interview sample (n = 31), representing all of our eligible respondents, is typical of qualitative studies (Guest, Bunce, & Johnson, 2006) and larger than, or on par with, recently published qualitative studies of EDs (Chubbs-Payne et al, 2021;Ortiz, Espel-Huynh, Felonis, & Scharff, 2020;Venturo-Conerly et al, 2020). Interviewees chose to provide their qualitative data via semi-structured telephone interviews (n = 19; 61.3%) or in writing (n = 12; 38.7%); interviewer prompts and clarification questions were identical for both response modalities.…”
Section: Current Studymentioning
confidence: 99%
“…However, even among individuals with binge‐spectrum EDs who exercise, there is considerable variability in the degree to which individuals engage in maladaptive exercise. For example, not all exercise episodes are necessarily maladaptive for a given individual (Chubbs‐Payne et al, 2021; Lampe, Forman, et al, 2021; Lampe, Trainor, et al, 2021). However, it is currently unknown to what extent exercise that is non‐maladaptive (i.e., not driven or compensatory) is overlapping with exercise that is adaptive (i.e., exercise promoting social or health benefits) in this population.…”
Section: Introductionmentioning
confidence: 99%